2013
DOI: 10.1657/1938-4246-45.2.190
|View full text |Cite
|
Sign up to set email alerts
|

Do P Cycling Patterns Differ Between Ice-Free Areas and Glacial Boundaries in the Maritime Antarctic Region?

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
0
1
0
1
Order By: Relevance
“…Releasing biogenic components from such soils is hindered (Simas et al 2006). However, Chacon et al (2013) showed that the less extreme microclimatic conditions and the presence of liquid water in the ice-free area promote the biogeochemical cycling of soil P. Soils of the area contain secondary minerals, such as haematite and the intergrade chlorite-vermiculite-montmorillonite. Similarly, N in these soils usually has the form of a salt (Bolter 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Releasing biogenic components from such soils is hindered (Simas et al 2006). However, Chacon et al (2013) showed that the less extreme microclimatic conditions and the presence of liquid water in the ice-free area promote the biogeochemical cycling of soil P. Soils of the area contain secondary minerals, such as haematite and the intergrade chlorite-vermiculite-montmorillonite. Similarly, N in these soils usually has the form of a salt (Bolter 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Таким чином, оліготрофних водойм у досліджуваному районі нами поки не виявлено. Водночас, за межами дослідженого району для антарктичного острова Кінг-Джордж біля поль-ської станції «Арцтовський» разом із місцями впливу великих колоній птахів, відомі олігомезотрофні прісні водойми, які відносно віддалені від узбережжя (Chacón et al, 2013).…”
Section: матеріали і методиunclassified